Blockchain Solution for Patient Record Security - Meher, Kunal (My University, 2024)
The presented Electronic Health Record (EHR) system aims to leverage blockchain technology to achieve enhanced security in transmission of data, improving data integrity, providing controlled access, interoperability, maximize productivity and empowering patients by empowering them to manage their health data. Blockchain system is recognized as a promising approach to these problems, providing a safe and decentralized platform for managing patient records. Our solution, which is built on blockchain technology, addresses critical issues in healthcare data management, such as unauthorized access, data tampering, and the absence of a unified and interoperable platform. By utilizing a distributed ledger, our system guarantees that patient data stays private while being easily available to authorized stakeholders. Smart contracts are utilized to govern access permissions and streamline the process of data sharing among healthcare providers, thereby facilitating a safe and efficient sharing of medical information. The presented EHR system utilize blockchain system to establish a protected, decentralized, and unchangeable record of patients’ medical histories. The system revolutionize the way health records are stored, accessed, and managed. By integrating Ethereum, Smart Contracts, and the Interplanetary File System (IPFS), the system ensures safe, transparent, and efficient handling of medical data. The integration of blockchain system into EHR systems has demonstrated considerable potential in mitigating some of the foremost obstacles within the domain. Due to its intrinsic decentralization, immutability, and openness, blockchain is the ideal tool for improving security, preserving data integrity, and building stakeholder trust in EHR systems.
uGDX
Keywords: HER Blockchain cybersecurity Information protection